The Impact of Consolidation on Islamic Financial Services Industry - Iqbal, Zamir (2012)
Small asset size of Islamic financial institutions (IFIs) is often cited as an obstacle for further growth. Looking at the motivating factors behind consolidation wave in conventional financial markets, this paper argues that IFIs can also benefit from consolidation in several ways. Expanding the scale of operations is not sufficient but it is essential that IFIs expand the scope of their products and services to meet the challenges of domestic and international markets. An increase in scale and scope through consolidation can provide IFIs necessary threshold to justify building a solid infrastructure for new services on both sides of the balance sheet. In addition to benefits of expanding scope, consolidation can bring benefits to IFIs through diversification and through enhanced management quality as well as efficiency gains from prudent risk taking, monitoring, and management. The paper concludes by discussing policy implication for policy-makers and the managers before embarking on the wave of consolidation.